ANALISIS PENGARUH WCTA, TAT, DR, ROA, SETA, SENSITIVITAS INFLASI, SENSITIVITAS KURS, DAN SENSITIVITAS SUKU BUNGA BI TERHADAP FINANCIAL DISTRESS (STUDI PADA PERUSAHAAN MANUFAKTUR 2010-2014) - Sativa, Amila; Prasetiono, Prasetiono (Faculty of Economics and Business Diponegoro University, 2016)
The purpose of this study is to analyze the influence of Working Capital to Total Assets (WCTA), Total Assets Turnover (TAT), Debt Ratio (DR), Return On Assets (ROA), Shareholder Equity to Total Assets (SETA), Inflation Sensitivity, Exchanger Rate Sensitivity, BI Interest Rate Sensitivity toward Financial Distress on manufacturing companies listed in BEI from 2010 to 2014. The sampling technique used in this study is purposive sampling technique using 95 manufacturing companies listed in BEI. Secondary data in this research using manufacturing companies financial reports during 2010-2014. The analysis technique is using logistic regression. The result of this research shows that WCTA, ROA, SETA, and BI Interest Rate Sensitivity had a negative and significantly influence on financial distress. Variable TAT had a negative and no significant effect on financial distress. Variable DR and Inflation Sensitivity had positive and no significant effect on financial distress. Variable Exchange Rate had positive significant effect on financial distress..